Hungary’s integration to European Union in a domestic and foreign historiography - Barkalova, Olha (Skhid, 2013)
The complex of the historiography in a fieldHungary’s political and economical integration into EU is analyzed in the given article. Author’s conception in a partition of historiography is also presented. The scientific works, which consider theoretical backgrounds of the EU functioning, main factors of theHungary’s eurointegration, fulfillment the EU criteria are also analyzed be the author.